Serum Serotonin Levels and the Severity Scores and Types of Delirium among Geriatric Patients in Denpasar, Indonesia - Kusnawan, I Made Dedy; Astika , Nyoman; Kurniawan, Lely Setyawati; Aryana , I Gusti Putu Suka (Current Internal Medicine Research and Practice Surabaya Journal, 2024)
Introduction: Delirium is an acute attention disorder that often occurs in elderly patients. The serotoninergic pathway is the main neurotransmitter pathway involved in the development of delirium. Serotonin, known as 5-hydroxythyramine (5-HT), affects mood, aggressiveness, cognition, depression, pressure, and stress in the brain environment. This may lead to the formation of hypoactive, hyperactive, or mixed delirium processes. This study utilized laboratory data with the aim of investigating whether serotonin levels have a correlation with severity score and delirium type in elderly individuals who experience delirium during hospitalization. Methods: This study was conducted in the field of geriatrics at Prof. Dr. IGNG Ngoerah Central General Hospital, Denpasar, Indonesia, from April 2022 to October 2023. The sample was gathered consecutively, consisting of 62 hospitalized geriatric patients who suffered from delirium and were willing to participate by signing an informed consent. We excluded post-surgical patients and psychoactive drug users. The data were collected using the Memorial Delirium Assessment Scale (MDAS), the Confusion Assessment Method (CAM), and a serum serotonin test. This study used bivariate analysis, the Kruskal-Wallis test, and Spearman’s correlation (p<0.05). Results: A total sample of 62 individuals was required. There was a significant difference in the mean serotonin levels among different types of delirium (p<0.05). Out of all the documented cases, hypoactive delirium was the most frequently observed (64.5%). Most of the elderly patients experienced severe delirium (54.8%). Serotonin levels had a significantly negative correlation with the MDAS scores (r=-0.95; p<0.001). Conclusion: The research findings indicate a correlation between lower serotonin levels and higher MDAS scores, and vice versa.   Highlights: 1. This study attempted to determine the relationship between serum serotonin levels and delirium severity scores among geriatric patients in Indonesia. 2. There was a significant difference in the mean serotonin levels among elderly individuals with hypoactive, hyperactive, and mixed types of delirium.